2018
DOI: 10.1001/jamainternmed.2018.0447
|View full text |Cite|
|
Sign up to set email alerts
|

Association of a Smartphone Application With Medication Adherence and Blood Pressure Control

Abstract: IMPORTANCE Medication nonadherence accounts for up to half of uncontrolled hypertension. Smartphone applications (apps) that aim to improve adherence are widely available but have not been rigorously evaluated.OBJECTIVE To determine if the Medisafe smartphone app improves self-reported medication adherence and blood pressure control. DESIGN, SETTING, AND PARTICIPANTSThis was a 2-arm, randomized clinical trial (Medication Adherence Improvement Support App For Engagement-Blood Pressure [MedISAFE-BP]). Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
294
6
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(342 citation statements)
references
References 39 publications
(66 reference statements)
10
294
6
11
Order By: Relevance
“…They may have been overestimated, as patients may not seek further medical follow-up after bariatric surgery, and may stop taking treatments despite persistent hypertension or high lipid levels. However, the same pattern is likely to occur in the control group, with obese patients not continuing to seek medical help, suggesting that the present comparisons are valid 33 .…”
Section: Discussionsupporting
confidence: 54%
“…They may have been overestimated, as patients may not seek further medical follow-up after bariatric surgery, and may stop taking treatments despite persistent hypertension or high lipid levels. However, the same pattern is likely to occur in the control group, with obese patients not continuing to seek medical help, suggesting that the present comparisons are valid 33 .…”
Section: Discussionsupporting
confidence: 54%
“…Several specialties across medicine are exploring this new communication mode to improve adherence and patient‐reported outcomes. Smartphone application use has been associated with an increase in medication adherence, enhanced sun protective behaviors, and improved post‐operative patient‐reported outcomes . GPower's application‐based take‐home technology could improve adherence by offering patients real‐time skin barrier function information.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prospective clinical studies have been previously conducted to measure the impact of digital solutions on chronic disease prevention and management; [36][37][38][39] however there have been a limited number of studies and solutions focused on older adults. In this study we observed high compliance and engagement with study-related activities (e.g., completion of RBANS tests, online assessments) and high engagement and satisfaction with the digital technology-based VC Health program for a population of older at-risk adults with SCD.…”
Section: Principal Resultsmentioning
confidence: 99%